Design and development of a cost effective WebVR commerce system prototype - Zainal Azmi, Nurazlin; Liem, Thomas Shiaw Hong (IIUM Press, 2025)
This project focuses on the design and development of a cost-effective WebVR commerce system prototype to enhance the online shopping experience. Despite the rapid growth of E-commerce, platforms face challenges such as limited interactivity, static product presentations, and lengthy purchasing procedures, which often lead customers to abandon online shopping in favor of physical stores. The proposed WebVR system leverages virtual reality to address these issues, providing an immersive and interactive shopping experience. By enabling users to visualize and explore products in a 3D virtual environment, the system bridges the gap between online and in-store shopping. However, virtual reality often requires costly hardware and powerful workstations to process the positioning data. Therefore, this project focuses on utilizing affordable technologies and frameworks to create a seamless and accessible solution, making WebVR a more practical option for a wider audience.